Reflections on the Socialization and Historicity of Female Childhood based on Costa Rican Tales between 1920 and 1940 - Sanabria León, Jorge Rafael (2024)
The models of childhood socialization narrated in Costa Rican tales of the 20th century make it possible to depict cultural patterns of socialization and their historicity. The reflection is oriented on the question of how the Costa Rican narrative represents notions of childhood and models of childhood socialization, in Costa Rican tales of the 20th century. The analysis from the in-depth Hermeneutics identified patterns of socialization, especially of female childhood, as a resource to intensify the drama of social processes in vogue during the time they cover. The findings are contrasted with theoretical premises derived from studies dealing with the historicity of childhood and the underlying sociocultural processes. The results reveal a childhood alien to leading processes in their interaction environments; subject to vertical control exercised by authority figures. Desirable characteristics such as child submission and obedience tend to be overestimated, and the lack of characterization of a social place in childhood with its own identity stands out. The notion of childhood is a metonymy that represents calamity and decadence, without a genuine questioning of its socio-familiar place.